The Association between Long Term Alcohol Consumption and Dementia - Dai, Baozhen; Marfoh, Joseph (International Journal of Medical and Health Sciences Research, 2021)
The study assessed the association between long-term alcohol consumption and risk of dementia in a panel study of 177 countries from 2000 to 2009. The study used econometric techniques to analyze the association between long-term alcohol consumption and risk of dementia. However, it employed the ordinary least square regression method and the fully modified ordinary least square regression method for robust inference. The study found that alcohol consumption is heterogeneously associated with dementia regarding the associated risk factors such as alcoholic disorder, anxiety disorder, depression disorder, bipolar disorder, and Schizophrenia. Moreover, some contributing factors such as age, eating disorder, smoking, and educational level play a significant role in attributing to dementia with the risk factor. However, it is recommended that alcohol consumption be reasonably taken to avoid its consequences. More specifically, ethanol is neurotoxic, crosses the blood-brain barrier to enter neurons directly, and can cause pathological processes leading to brain damage in high concentrations and its metabolite acetaldehyde.